Pengaruh Gaya Kepemimpinan dan Pemanfaatan Teknologi Informasi pada Kualitas Laporan Keuangan Desa - Basudewa, I Gede Teo; Asri Dwija Putri, I G. A. M. (E-Jurnal Akuntansi, 2020)
The purpose of this study was to determine the effect of leadership style and the use of information technology on the quality of village financial reports. This research was conducted in all villages in the city of Denpasar. The number of villages used is 27 villages and the number of sampels used is 180 people, with the purposive sampling method the respondents chosen must know the management of village funds. The analysis technique used is multiple linear regression. Based on the analysis revealed that the leadership style and the use of information technology have a positive effect on the quality of village financial reports. The use of information technology has a positive and significant effect on the quality of village financial reports. Keywords: Leadership Style; Utilization of Information Technology; Quality of Village Financial Reports.